Developing Peer Learning-Based Communication Simulation E-Modules to Enhance Soft Skills in Office Management Vocational Education - Selvy Kusumaningrum; Nina Oktarina; Agung Kuswantoro (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop an interactive e-module integrated with peer learning and workplace communication simulations to enhance students’ communication skills. The research employed a Research and Development (R&D) method using the 4D model—Define, Design, Develop, and Disseminate. The product was validated by two subject matter experts and one media expert, and its effectiveness was tested through limited trials and expanded trials involving 60 students using pretest and posttest scores. Data were analyzed using quantitative and descriptive qualitative techniques. Qualitative data in the form of suggestions and feedback from validators were used to improve the e-module. Meanwhile, quantitative data were obtained from validation scores, teacher assessments, and student test results, which were analyzed to measure the feasibility and effectiveness of the product. The e-module received a validity score of 96% from content experts and 100% from the media expert, indicating high feasibility. Effectiveness trials showed a significant improvement in students’ learning outcomes, with an average N-Gain of 0.751 in the limited trial and 0.791 in the expanded trial. Practical communication skills, including oral communication and workplace communication ethics, improved substantially, with simulation performance scores averaging 90.667 and 90.800 in two different classes. These results confirm the effectiveness of the interactive e-module in supporting the teaching of workplace communication and enhancing students’ real-world communication competencies. Students’ negotiation and persuasion skills showed the most significant improvement among the communication aspects assessed. Therefore, the developed module is suitable for use as a digital learning tool in vocational Office Management programs.